If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.4x + -1(x + 0.3333333333) = 0.06666666666(x + 1) Reorder the terms: 0.4x + -1(0.3333333333 + x) = 0.06666666666(x + 1) 0.4x + (0.3333333333 * -1 + x * -1) = 0.06666666666(x + 1) 0.4x + (-0.3333333333 + -1x) = 0.06666666666(x + 1) Reorder the terms: -0.3333333333 + 0.4x + -1x = 0.06666666666(x + 1) Combine like terms: 0.4x + -1x = -0.6x -0.3333333333 + -0.6x = 0.06666666666(x + 1) Reorder the terms: -0.3333333333 + -0.6x = 0.06666666666(1 + x) -0.3333333333 + -0.6x = (1 * 0.06666666666 + x * 0.06666666666) -0.3333333333 + -0.6x = (0.06666666666 + 0.06666666666x) Solving -0.3333333333 + -0.6x = 0.06666666666 + 0.06666666666x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.06666666666x' to each side of the equation. -0.3333333333 + -0.6x + -0.06666666666x = 0.06666666666 + 0.06666666666x + -0.06666666666x Combine like terms: -0.6x + -0.06666666666x = -0.66666666666x -0.3333333333 + -0.66666666666x = 0.06666666666 + 0.06666666666x + -0.06666666666x Combine like terms: 0.06666666666x + -0.06666666666x = 0.00000000000 -0.3333333333 + -0.66666666666x = 0.06666666666 + 0.00000000000 -0.3333333333 + -0.66666666666x = 0.06666666666 Add '0.3333333333' to each side of the equation. -0.3333333333 + 0.3333333333 + -0.66666666666x = 0.06666666666 + 0.3333333333 Combine like terms: -0.3333333333 + 0.3333333333 = 0.0000000000 0.0000000000 + -0.66666666666x = 0.06666666666 + 0.3333333333 -0.66666666666x = 0.06666666666 + 0.3333333333 Combine like terms: 0.06666666666 + 0.3333333333 = 0.39999999996 -0.66666666666x = 0.39999999996 Divide each side by '-0.66666666666'. x = -0.5999999999 Simplifying x = -0.5999999999
| 4(f+3)=17+4f | | -13b+b=31 | | 15x-35+-8x-36=43 | | x^3-250=0 | | 5(10^3)/15(10^2) | | w+5z=-3 | | 8y+168=7x | | x^3-6x^2+9x-8=0 | | 5-3x=x+5-4x | | 7f-f+3g+15= | | 13.5/1.5 | | 1-n-3n=-15 | | 6x+7(x-7)=16 | | 8y+168=x | | 15y+x= | | 3a-3=-a+5 | | 8-3(4x-1)=49 | | 10b-2b=8 | | D-17=31 | | 18+128x^2=0 | | -(7)-y=-8 | | .75x-.68x=.4 | | 0=3x^2-23x+30 | | -2÷-4/5 | | 10-6x=-4x+4 | | 2msquared+16=10m | | n/1.5=9 | | X^4+x^3-27x^2-3x-90=0 | | -4(3x-9)=8(-8-x) | | (-5x)+(-215)-(5x)+(21.5)= | | 3(3x-3)+2x=0 | | $200,000-1/10 |